2022
DOI: 10.3390/antibiotics11101407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Single Dose Enrofloxacin Injection on Development of Fluoroquinolone Resistance in Campylobacter jejuni in Calves

Abstract: Fluoroquinolone (FQ) resistance in a major foodborne bacterial pathogen, Campylobacter jejuni, derived from cattle has recently become prevalent and poses a significant public health concern. However, the underlying factors for this increase are not entirely clear. To evaluate the effect of enrofloxacin treatment on FQ-resistance development in C. jejuni, 35 commercial calves were equally divided into five groups (Groups 1–5) and were orally inoculated with FQ-susceptible (FQ-S) C. jejuni. Eight days later, Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…In chickens, as soon as 24 h after treatment with FQ antibiotics (enrofloxacin, sarafloxacin, or difloxacin; typically given in drinking water for 5 days), FQ-R Campylobacter mutants were found in the feces of treated birds and gradually colonized the intestinal tract at high densities ( 34 , 56 , 57 ). In big contrast, our recent study with calves showed that a single dose s.c. enrofloxacin treatment (7.5 or 12.5 mg/kg) did not result in any detectable level of FQ resistance development from FQ-S C. jejuni inhabiting the intestine ( ~ 10 4–5 CFU/g feces) of calves ( 46 ). Similarly, therapeutic administration of neither oral (20 mg/kg daily for 7 days) nor subcutaneous (20 mg/kg daily for 1–7 days) enrofloxacin resulted in development FQ-resistance in C. jejuni NCTC 11168 following experimental inoculation of mice via oral gavage ( 69 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In chickens, as soon as 24 h after treatment with FQ antibiotics (enrofloxacin, sarafloxacin, or difloxacin; typically given in drinking water for 5 days), FQ-R Campylobacter mutants were found in the feces of treated birds and gradually colonized the intestinal tract at high densities ( 34 , 56 , 57 ). In big contrast, our recent study with calves showed that a single dose s.c. enrofloxacin treatment (7.5 or 12.5 mg/kg) did not result in any detectable level of FQ resistance development from FQ-S C. jejuni inhabiting the intestine ( ~ 10 4–5 CFU/g feces) of calves ( 46 ). Similarly, therapeutic administration of neither oral (20 mg/kg daily for 7 days) nor subcutaneous (20 mg/kg daily for 1–7 days) enrofloxacin resulted in development FQ-resistance in C. jejuni NCTC 11168 following experimental inoculation of mice via oral gavage ( 69 ).…”
Section: Discussionmentioning
confidence: 97%
“…Cattle are a significant source of human Campylobacter infections, and there is a clear trend that FQ-R Campylobacter from cattle has become highly prevalent in recent years ( 7 , 15 , 62 , 63 ). Even though the selection pressure (use of FQs in cattle) may have contributed to the expansion of FQ-R Campylobacter , the actual impact of this factor appears to be rather low ( 32 , 44 , 46 , 64 ). In the current study, we examined the hypothesis that the fitness of FQ-R Campylobacter may have also played a role in the rise seen in FQ-R Campylobacter isolates of cattle origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different from sheep production where the use of FQ antimicrobials is prohibited, FQs are used for the treatment and control of respiratory diseases in cattle [63]. The use of FQ antimicrobials could serve as a selection force for the spread of FQ-resistant Campylobacter, but a recent FQ treatment study suggested that subcutaneous injection of FQ antimicrobials did not result in the de novo development of FQ-resistant mutants from the inoculated FQ-susceptible C. jejuni in the cattle intestinal tract [64]. As explained by the authors, this might be due to the relatively low density of Campylobacter in cattle feces and the high concentration of the antimicrobial excreted into the intestine [65], which could have exceeded the mutant selection window and prevented the emergence of FQ-resistant mutants.…”
Section: Fluoroquinolone (Fq) Resistance In Campylobacter: a One Heal...mentioning
confidence: 99%